Frontiers of propulsion science - Millis, Marc G.; Davis, Eric W. (American Institute of Aeronautics and Astronautics, 2009)
This books is the first compilation of emerging science relevant to such notions as space drives, warp drives, gravity control, and faster-than-light travel - the kind of breakthroughs that would revolutionize spaceflight and enable human voyages to other star systems. Although these concepts might sound like science fiction, they are appearing in growing numbers in reputable scientific journals.
Keywords: Space vehicles -- Propulsion systems.; Space flight.; Astronautics.; Space flights.; elektronické knihy; electronic books